Subareolar breast abscess in male patients: a report of two patients with a literature review - Kazama, Takashi (Surg Case Rep, 2017)
BACKGROUND: Subareolar breast abscess (SBA) is a rare infectious disease of the breast in male patients. CASE PRESENTATION: Herein, we report two male patients with SBA. Patient 1 was initially diagnosed with a malignant tumor based on imaging findings; ultrasonography revealed a hypoechoic mass with blood flow. Patient 2 was diagnosed with inflammatory changes to his nipple; ultrasonography findings supported the diagnosis with an irregular hypoechoic mass with blood flow. Both patients received a cytological or histological biopsy preoperatively, which showed an abscess without malignant cells. CONCLUSION: These cases serve as an important reminder to consider complete resection of the tumor including the responsible mammary duct (tumor and duct resection (TDR)) for curative therapy of SBA.